Brief exposure of juvenile rats to noise impairs the development of the response properties of inferior colliculus neurons - Grécová, Jolana; Bures, Zbynek; Popelár, Jirí; Suta, Daniel; Syka, Josef (The European journal of neuroscience, 2009)
Temporary impairment of the auditory periphery during the sensitive period of postnatal development of rats may result in a deterioration of neuronal responsiveness in the central auditory nuclei of adult animals. In this study, juvenile rats (postnatal day 14) were exposed for 8 min to intense broad-band noise; at the age of 3-6 months, the excitatory and inhibitory response areas of neurons in the central nucleus of the inferior colliculus were recorded under ketamine-xylazine anaesthesia in these animals and compared with those of age-matched controls. The response thresholds were similar in the exposed and control animals. The frequency selectivity of low-frequency neurons was comparable in both groups; however, high-frequency neurons had significantly wider excitatory response areas in the exposed rats, indicating disrupted development of high-frequency hearing. Forty-one per cent and 25% of neurons in exposed animals and in controls, respectively, lacked a distinct inhibitory area; these neurons had similar frequency selectivity in the exposed and control rats. As the presence of an inhibitory sideband was associated with sharper frequency tuning in both groups, it appears that lateral inhibition substantially influences neuronal frequency selectivity. If present, the inhibitory areas had comparable bandwidths in both groups; however, they were shifted to the side in the exposed animals, allowing the expansion of the excitatory areas. The results indicate that a brief exposure of juvenile rats to noise leads to a significant worsening of the frequency selectivity of inferior colliculus neurons in adult animals; the poorer frequency selectivity may be due to missing or displaced inhibitory sidebands.
Keywords: Neurons; Rats; otoakustické emise spontánní; Evoked Potentials, Auditory, Brain Stem; potkani Long-Evans; Auditory Threshold; mikroelektrody; sluchová percepce; Inferior Colliculi; regresní analýza; sluchový práh; krysa rodu Rattus; zvířata; Acoustic Stimulation; colliculus inferior; neurony; Rats, Long-Evans; sluchové kmenové evokované potenciály; Otoacoustic Emissions, Spontaneous; Auditory Perception; akustická stimulace; Regression Analysis; Microelectrodes; Animals